The Effectiveness of Project-Based Learning Toward Students' Speaking Performance and Skill - Agustin N H Wijaya; Umar Al Faruq A Hasyim; Mai Zuniati; Marzia Khatan Smita; Suhono; Irhamudin (Attractive : Innovative Education Journal, 2025)
This article aims to investigate the impact of Project-Based Learning (PBL) on the speaking performance and skills of second-semester students in the English Study Program at Universitas Ma’arif Lampung. PBL was employed in this study to address issues encountered in speaking classes. A pre-test was administered to 18 students from the English Study Program as part of the research conducted in March 2024. The analysis of the pre-test revealed a mean score of 54.89, with a standard deviation of 7.738 and a sample size of 18, alongside a minimum score of 44 and a maximum score of 64. The post-test results indicated an increase in the average score of students taught using PBL, suggesting a significant enhancement in both their performance and speaking skills attributable to the project-based learning approach. This underscores the efficacy of this method in yielding notable differences between pre-test and post-test results. The implementation of PBL in speaking instruction encompasses several phases, including the formulation of a project strategy, the establishment of a timeline, monitoring the progress of students and the project, analysing outcomes, and evaluating the overall experience.